Beneficial effects of Annona squamosa extract in streptozotocin-induced diabetic rats - Kaleem, Mohammed; Medha, P.; Ahmed, Qamar Uddin; Asif, Mohd S.; Bano, Bilqees (Singapore Medical Association, 2008)
Introduction: The present study investigated the possible therapeutic effects of Annona squamosa (A. squamosa) extract on certain biochemical markers in streptozotocin (STZ) -induced diabetes mellitus in rats. Methods: The effects of an aqueous extract of A. squamosa leaves on blood glucose, insulin, C-peptide, albumin, albumin/globulin ratio, urea, uric acid and creatinine and the activities of diagnostic marker enzymes aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase and gamma-glutamyl transpeptidase were examined in the plasma, liver and kidney tissues of control and experimental groups. Results: Oral administration of A. squamosa (300 mg/kg) aqueous extract to diabetic rats for 30 days significantly reduced blood glucose, urea, uric acid and creatinine, but increased the activities of insulin, C-peptide, albumin, albumin/globulin ratio and restored all marker enzymes to near control levels. Conclusion: The present results shown that A. squamosa extract has an antihyperglycaemic effect and consequently may alleviate liver and renal damage associated with STZ-induced diabetes mellitus in rats.